K.Marx-Engels and Ho Chi Minh Viewpoints on Journalism - and Two Fake News Publishing Cases of Thanhnien.vn and Tuoitre.vn (Online Magazines) in Vietnam and Lessons from Indonesia, Japan Approaches - Dinh Tran Ngoc Huy; Le Huong Hoa; Bui Thi Thu; Dinh Tran Ngoc Hien (Journal La Sociale, 2022)
In this paper, by using qualitative analytical analysis with 2 case examples of Thanh nien and Tuoi tre newspapers (online) in Vietnam, in which there are history of publishing fakes news online from 2015, 2016, 2018, 2022 (with very bad editors Nguyen Ngoc Toan and Dang Thi Phuong Thao), as well as giaoduc.edu.vn and vietnamnet.vn in 2022 so we will address some points in this study based on answers for question: “What are regulatory lessons from Indonesia and Japan approaches on publishing fake news?”. We would suggest that there are penalties for negative behaviors of posting fake news online (any fake information) in the context of covid 19 epidemic. Tapsell (2019) defined ‘hoax news’ as similar to the more globally recognized term ‘fake news’: material deliberately fabricated and masqueraded as truth. At last, we will draw some lessons from K.Marx and Ho Chi Minh viewpoints on journalism for educating young generation in emerging markets such as Vietnam.